Analisis Penjatuhan Pidana Pelayanan Masyarakat terhadap Anak yang Berkonflik dengan Hukum untuk Terwujudnya Tujuan Pemidanaan - Setyorini, Annisa; Siswanto, Heni; Fathonah, Rini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The imposition of community service as a conditional punishment for children in conflict with the law is a form of restorative justice aimed at rehabilitation rather than retribution. This study focuses on judicial considerations in sentencing community service for child offenders, specifically in District Court Decision No. 59/Pid.Sus-Anak/2024/PN.Tjk, and whether such punishment aligns with the objectives of criminal sentencing. This research adopts a normative and empirical juridical approach, using legal literature and field interviews with judges, prosecutors, and community counselors as primary sources. Data were analyzed qualitatively. The findings reveal that the judge's decision to impose community service is legally grounded in Article 71(1)(c) of the Juvenile Criminal Justice System Law (UU SPPA), which permits alternative sanctions for child offenders. Philosophically, the sentence aims to reform and educate the child, while sociologically, the court considers both mitigating and aggravating factors, such as the child’s background, remorse, and potential for rehabilitation. The type of service assigned, such as assisting with administrative tasks at a local government office, reflects efforts to promote social responsibility. Furthermore, the imposed punishment fulfills the objectives outlined in Article 51 of the Indonesian Criminal Code, including deterrence, reintegration, conflict resolution, and community peace. Overall, the use of community service supports a more humanistic, child-centered approach to juvenile justice in Indonesia.